(untitled) (University Arena, 2025)
Premises. During the physical education Karate-Do lessons and also for the grade examination for the yellow belt at the end of the first year of University, the students will include in their current practice the pre-established five steps fighting exercises (Japanese: Gohon Kumite). Progress in Karate-Do will be established the same as in others physical education disciplines, following the principle of accessibility, by applying the three classical rules of didactic practice: from easy to difficult, from simple to complex and from known to unknown. The first step of Karate-Do is to correctly learn the fighting techniques by exercising alone, without a partner (Jap.: Kihon). The second step is to apply them by fighting one or more adversaries (Jap.: Kumite). By practicing the fighting exercises with a Karate-Do partner one can also attain the specific principals of physical education, by bettering physical development and motric capacities. A very important factor during the physical exercises will be the mental side, the student developing in short time understanding for the other side, for the activity immersion, for controlling emotions and techniques, for focusing one’s mind better and for will strength and developing a fighting spirit. Objectives. Internalizing the basic techniques for attacking and defense, controlling the breathing techniques, moving the body in the right sequence. Mentally, we will look for controlling emotions, fighting spirit, trusting yourself and determination. Methods. The method used for this presentation concerning the specific Gohon Kumite exercises, practiced by the Japan Karate Association will also be used by the students of The University of Bucharest in the first year of studies. The fore mentioned practice techniques are available for all the basic techniques to help attain the desired objectives. Conclusions. During the lessons with the students of the University of Bucharest, an important step is fighting one or more partners, following the Gohon Kumite exercises. By exercising these techniques, students will develop mental capacity, motric qualities, rhythm, breathing and following the right steps to attain the right techniques. Corectly practiced, the Gohon Kumite exercises will form a solid base for the next fighting techniques needed in superior levels of instruction and knowledge, by helping the formation of a strong fighting spirit and a strong, focused mind.